Peculiarities of the adsorption kinetics of mixed convex plus concave contour objects - Shelke, Pradip B.; Ogale, S. B.; Khandkar, M. D.; Limaye, A. V. (Physical Review E, 2008)
Random sequential adsorption of mixed convex plus concave contour (MC) objects exhibits some distinctly different peculiar characteristics than the cases of purely convex objects. Though the substrate coverage approaches the jamming limit with time t as t(-p), same as that for convex objects, the law p similar to 1/d(f), valid for convex objects with d(f) degrees of freedom, does not hold for MC objects. Interestingly, for a fixed number of degrees of freedom, the exponent p changes with the degree of nonconvexity and bears a near perfect correlation with the same.